SECURITY AND SAFETY FOR SUSTAINABILITY IN AVIATION INDUSTRY : SECURITY AND SAFETY FOR SUSTAINABILITY IN AVIATION INDUSTRY - Wahyudi, Dian; Hamzah, Muhammad Zilal (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
In an era of advancing technology, air transportation has become the preferred mode of transport due to its efficiency. As air transportation continues to develop, issues related to aviation safety and security have become crucial in the aviation industry. Hence this study have a several objectives: (i). To analyse the impact of implementing the SSR towards security aspects; (ii). To analyse the impact of implementing SSR for economy; and (iii). Describing the rate of violation before and after the implementation. This study using a Systematic Literature Review (SLR) based on Web of Science (WOS) databased with several criteria. This study finds that technology is an important aspect for enhancing the security, however in the economics perspectives profitability of the airlines affect managerial decisions that might be influence the service quality. The security aspect is also affecting the competitiveness among airlines. The other findings are human capital are the most important aspect to support the security aspect.